Creating a world on paper : Harry Fenn's career in art - Rainey, Sue (UPCC book collections on Project MUSE., 2013)
Harry Fenn was one of the most skilled and successful illustrators in the United States in the latter half of the nineteenth century, a time when illustrated periodicals and books were the primary means of sharing visual images. Fenn’s work fostered pride in America’s scenic landscapes and urban centers, informed a curious public about foreign lands, and promoted appreciation of printed pictures as artworks for a growing middle class. This volume documents Fenn’s prolific career from the 1860s until his death in 1911. The author also recounts Fenn's adventurous sketching trips in the western United States, Europe, and the Middle East, which enhanced his reputation for depicting far-flung places at a time when the nation was taking a more prominent role on the world stage.